Fighting for the right to use wastewater: what drives the use of untreated wastewater in a peri-urban village of Faisalabad, Pakistan? - Weckenbrock, P.; Evans, Alexandra E.V.; Majeed, M.Q.; Ahmad, Waqas; Bashir, N. (Informa UK Limited, 2011)
This case study from Chakera village, Faisalabad City, Pakistan describes the transition from canal-water irrigation to wastewater irrigation over a period of several decades. It shows that while the initial motivation for wastewater use was water scarcity and a lack of choice, farmers soon realized there were benefits associated with this alternative water supply. In the subsequent decades, they made great efforts and overcame organizational, infrastructural and legal obstacles to establish wastewater irrigation as the only irrigation on most of the village's agricultural area.